2008
DOI: 10.1103/physrevlett.101.264501
|View full text |Cite
|
Sign up to set email alerts
|

Universality in Oscillating Flows

Abstract: We show that oscillating flow of a simple fluid in both the Newtonian and the non-Newtonian regime can be described by a universal function of a single dimensionless scaling parameter omega tau, where omega is the oscillation (angular) frequency and tau is the fluid relaxation time; geometry and linear dimension bear no effect on the flow. Energy dissipation of mechanical resonators in a rarefied gas follows this universality closely in a broad linear dimension (10(-6) m < L < 10(-2) m) and frequency (10(5) Hz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…Therefore, we believe that it is of a great importance to improve the Q-factors in aqueous environment for bio-sensing applications such as in situ, real-time detection. Recent progress towards understanding Qfactor degradation due to surrounding fluidic environments has occurred due to work by Ekinci et al [185,186], who studied doubly clamped silicon beam resonators in a gaseous nitrogen environment. They found that fluidic dissipation appears to saturate at high frequencies that are related to the relaxation times of the fluid; this finding enabled them to quantitatively state how the NEMS geometry can be utilized to minimize fluidic dissipation.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…Therefore, we believe that it is of a great importance to improve the Q-factors in aqueous environment for bio-sensing applications such as in situ, real-time detection. Recent progress towards understanding Qfactor degradation due to surrounding fluidic environments has occurred due to work by Ekinci et al [185,186], who studied doubly clamped silicon beam resonators in a gaseous nitrogen environment. They found that fluidic dissipation appears to saturate at high frequencies that are related to the relaxation times of the fluid; this finding enabled them to quantitatively state how the NEMS geometry can be utilized to minimize fluidic dissipation.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…For bulk fluids, by contrast, direct mechanical observation of non-Newtonian behavior has been limited to solid structures interacting with dilute gases [14]. In this case, the effects can be predicted rigorously by the Boltzmann equation [15].…”
mentioning
confidence: 99%
“…16 For an oscillating flow, a measure of the importance of molecular scale dynamics is given by the Weissenberg number Wi ¼ xs where x is the frequency of oscillation of the nanobeam and s is the fluid relaxation time scale. 22 For atmospheric air s % k=c % 0:2 ns where k is the mean free path of a fluid molecule between collisions and c is the speed of sound. For the resonator considered here, in atmospheric air, this yields Wi % 0:01 ( 1 which indicates that the flow field can be treated as a continuum.…”
Section: Resultsmentioning
confidence: 99%
“…For the resonator considered here, in atmospheric air, this yields Wi % 0:01 ( 1 which indicates that the flow field can be treated as a continuum. 22 Although we have not explored this aspect further, we emphasize that it would be possible to use our general approach with a latticeBoltzmann solver 23,24 for the fluid-solid interactions to quantify the dynamics in the Wi տ 1 limit if desired.…”
Section: Resultsmentioning
confidence: 99%